2019
DOI: 10.3988/jcn.2019.15.3.369
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Response to First-Line Treatments in Patients with Anti-N-Methyl-D-Aspartate Receptor Encephalitis

Abstract: Background and Purpose Anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis is the most common type of autoimmune encephalitis. This study aimed to explore the possible factors affecting the response to first-line treatments in patients with anti-NMDAR encephalitis. Methods We enrolled 29 patients who were diagnosed as anti-NMDAR encephalitis between January 1, 2015, and June 30, 2018. They were divided into the remission and nonremission groups according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
3
18
0
Order By: Relevance
“…The optimal NLR value to predict mRS >1 was identified as 4.45 (AUC 0.866). A third retrospective study of 29 patients with anti-NMDAR encephalitis found that the median NLR was significantly higher in non-responders to first line immunotherapy than in responders, both before (4.10 vs 2.39) and after (4.14 vs 2.62) treatment ( 11 ). The results from our study support the above observations, with 1.3-fold increase in odds of treatment failure for every rise in the NLR by 1 unit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal NLR value to predict mRS >1 was identified as 4.45 (AUC 0.866). A third retrospective study of 29 patients with anti-NMDAR encephalitis found that the median NLR was significantly higher in non-responders to first line immunotherapy than in responders, both before (4.10 vs 2.39) and after (4.14 vs 2.62) treatment ( 11 ). The results from our study support the above observations, with 1.3-fold increase in odds of treatment failure for every rise in the NLR by 1 unit.…”
Section: Discussionmentioning
confidence: 99%
“…In MS, the NLR has been demonstrated to correlate with disease progression and worse disability outcomes ( 7 9 ). Recent studies in AE have found that a high NLR is significantly correlated with long-term functional disability as measured by the mRS and reduced response to first line immunotherapy ( 10 , 11 ). The monocyte-to-lymphocyte (MLR) has recently been associated with disability scores in MS ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, antibody titer was not an independent predictor of poor short-term first-line treatment response by multivariate analysis. In our previous study, we also did not find an association between the antibody titers and treatment response in anti-NMDAR encephalitis patients ( 22 ). At present, studies on the relationship between antibody titer and patients with AE are inconsistent.…”
Section: Discussionmentioning
confidence: 54%
“…Recently, studies found that NLR may be a biomarker to monitor disease progression in patients with AE ( 3 , 33 ). Our team also found that it is associated with the first-line treatment response in anti-NMDAR encephalitis ( 22 ). In this study, we found that higher NLR level was associated with non-response to short-term first-line treatment in patients with AE, and in anti-NMDAR subtype encephalitis patients.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation